Programa “LUDIMAT” para mejorar la noción de clasificación en niños de 4 años de la I.E. Nº 80057-Paiján, 2017 - Laguna Eusebio, Marleni Angelica (2020)
ABSTRACT This research entitled program LUDIMAT TO IMPROVE THE NOTION OF CLASSIFICATION IN CHILDREN 4 YEARS OF I.E. Nº 80057- PAIJAN,2017. aims to improve the notion of classification in boys and girls. Through of recreational actvities will motivate students to develop learning of the notion of classification of funny way. The research is of quasi experimental with design of pre and post test with two groups: Experimental and control. The population was formed by 71 boys and girls, considering a sample of 36 boys and girls, 18 children in the red classroom and 18 children in the orange classroom, to which a pre-test was applied to know the level of notion of classification. The results of the pre-test show that students from both sections (control and experimental) had difficulty in developing the notion of classification. The results obtained in the pre test of the experimental group was an average of 5,67 (in anset) presenting deficiencies in the notion of classification. After having aplplied the program LUDIMAT, with the realization of didactic activities basically play in the experimental group, the boys and girls showed an increase significant in post test results with an average of 18,00 ranking at one level of expected achievement, concluding that the aplication of the programme influences the improvement of the notion of classification in boys and girls of 4 years of I.E. Nº 80057-Paijan.